Implementation Of The Diversion Policy On Child As A Criminal Based On Justice Value - Nur Azizah; Ira Alia Maerani (Law Development Journal, 2021)
The purpose of this study is to examine and analyze the application of diversion policies against children as perpetrators of crimes that have not been fair, the obstacles in implementing diversion policies against children as perpetrators of crimes and the application of diversion policies against children as perpetrators of crimes based on the value of justice in the future. This study uses a sociological juridical approach, with analytical descriptive research methods. The data used are primary and secondary data which will be analyzed qualitatively. The research problem was analyzed using the theory of justice and the theory of expediency. The results of the study concluded that the application of diversion in handling crimes committed by children at the Central Java Regional Police through a family deliberation process. The application has not been fair because all criminal cases of children have not all been carried out with diversion efforts. The obstacles encountered in the application of diversion in handling criminal acts by children at the Central Java Regional Police are: 1) Threats of criminal acts with sanctions of 7 years and over. 2) Problems Appear If Parents Are Community Leaders 3). The existence of intervention on the side of the victim. 4). Lack of Optimal Ability of Investigators in Implementing Diversion Policy.5). There is no common ground and agreement between the victim and the perpetrator. The solutions to the obstacles faced are: 1) The threat of imprisonment is reviewed. 2). If parents, community leaders must be cooperative. 3). Need to eliminate intervention from any party. 4). Optimization of investigator capabilities. 5). Efforts to mediate between the victim and the perpetrator. The application of the diversion policy in the future is that diversion must consistently be carried out in child crimes.